Goethe yearbook, Volume XII publications of the Goethe Society of North America - Richter, Simon (Boydell & Brewer, 2004)
The 'Goethe Yearbook,' first published in 1982, is a publication of the Goethe Society of North America and is dedicated to North American Goethe scholarship. It aims above all to encourage and publish original English-language contributions to the understanding of Goethe and other authors of the 'Goethezeit,' while also welcoming contributions from scholars around the world. The book review section seeks likewise to evaluate a wide selection of recent publications on the period, and is important for all scholars of 18th-century literature. Volume 12 honors founding editor Thomas P. Saine with contributions from prominent scholars such as Ehrhard Bahr, Benjamin Bennett, Dieter Borchmeyer, Jane Brown, Jill Kowalik, Ruth Kluger, Meredith Lee, John McCarthy, Jeff Sammons, Helmut Schneider, Hans Vaget, and more. The volume includes essays on Goethe's novels, plays, and poems, the Ilmpark, Bach, Ossian, Goethe reception, and Schiller. Simon J. Richter is associate professor of German and Comparative Literature at the University of Pennsylvania. Book review editor Martha B. Helfer is associate professor of German at the University of Utah